The Role of Macrophages in the Pathogenesis of ALI/ARDS - Xiaofang Huang; Huiqing Xiu; Shufang Zhang; Gensheng Zhang (Mediators of Inflammation)
Despite development in the understanding of the pathogenesis of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), the underlying mechanism still needs to be elucidated. Apart from leukocytes and endothelial cells, macrophages are also essential for the process of the inflammatory response in ALI/ARDS. Notably, macrophages play a dual role of proinflammation and anti-inflammation based on the microenvironment in different pathological stages. In the acute phase of ALI/ARDS, resident alveolar macrophages, typically expressing the alternatively activated phenotype (M2), shift into the classically activated phenotype (M1) and release various potent proinflammatory mediators. In the later phase, the M1 phenotype of activated resident and recruited macrophages shifts back to the M2 phenotype for eliminating apoptotic cells and participating in fibrosis. In this review, we summarize the main subsets of macrophages and the associated signaling pathways in three different pathological phases of ALI/ARDS. According to the current literature, regulating the function of macrophages and monocytes might be a promising therapeutic strategy against ALI/ARDS.